2019
DOI: 10.1186/s12885-019-6190-3
|View full text |Cite
|
Sign up to set email alerts
|

Cancer care in Brazil: structure and geographical distribution

Abstract: BackgroundThe organisation and systematisation of health actions and services are essential to ensure patient safety and the effectiveness and efficiency of cancer care. The objective of this study was to analyse the structure of cancer care envisaged in Brazilian norms, describe the types of accreditations of cancer services and their geographic distribution, and determine the planning and evaluation parameters used to qualify the health units that provide cancer care in Brazil.MethodsThis observational study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 36 publications
2
34
0
11
Order By: Relevance
“…In Brazil, the cancer treatments are performed in specialized care units, in both the public and private sectors. According the current system regulation, these services should be distributed among administrative health regions, according to population criteria [6]. The SUS finances the major part of cancer care in Brazil, due the large costs of treatment [7].…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, the cancer treatments are performed in specialized care units, in both the public and private sectors. According the current system regulation, these services should be distributed among administrative health regions, according to population criteria [6]. The SUS finances the major part of cancer care in Brazil, due the large costs of treatment [7].…”
Section: Introductionmentioning
confidence: 99%
“…Its creation represented an increase in the supply of services, but regional differences, underfunding, changes in the age structure of the population and changes in its health conditions compromise its effectiveness [ 37 ]. Silva et al [ 38 ] showed that the provision of specialised services for cancer is still deficient in the country. The low survival rate in the study region may reflect the difficulty in accessing health services, when existent, due to social, economical, cultural and information barriers.…”
Section: Discussionmentioning
confidence: 99%
“…The regions with the most qualified health care facilities are in the South and the Southeastern Brazil, accounting for more than two thirds of centers, as compared with three other regions that have < 10% each. 11 This inequality in resource distribution leads to important restrictions in diagnosis, staging, and comprehensive treatment. Additionally, conflicting regulations in specific areas of cancer care, insufficient funding of cancer programs, weak epidemiologic surveillance, and unclear pathways for patients with cancer increase barriers for adequate care.…”
Section: Methodsmentioning
confidence: 99%